Production of L-Arginine from arginine analogue resistant mutants of Corynebacterium glutamicum - Musini, Anjaneyulu; Mangamoori, Lakshmi Narasu; Saida, L. (International Journal of Scientific Research in Biological Sciences, 2018)
L-arginine is an essential amino acid, widely used in pharmaceutical, feed and food industry. It is the precursor molecule in citrulline and nitric oxide synthesis, which in turn plays significant role in a wide variety of patho - physiological functions in the cardiovascular, central and peripheral nervous systems. In the present study, mutagenesis experiments were carried out for isolation of analogue resistant mutants against Corynebacterium glutamicum. Initially, MIC (Minimum inhibitory concentration) was identified for arginine analogues by tube dilution method. MIC values found to be Arginine hydroximate – 680 µg/ml. Further, mutagenesis of C. glutamicum was carried out with NTG (300µg/ml) and amino acid analogue resistant mutants were isolated in minimal media. Fermentation was carried out by resistant colonies and estimated the Arginine levels. Production level was found to be 5.2 mg /ml where as in control cells it was 1.4 mg /ml. This study highlighted the C. glutamicum mutant of L-arginine amino acid production.